KEANEKARAGAMAN DAN KELIMPAHAN BURUNG AIR DI MUARA SUNGAI KAWASAN SEGARA ANAKAN CILACAP, JAWA TENGAH - Elisabet RRB Hutabarat; Ani Mardiastuti; Yeni A. Mulyani (Media Konservasi, 2016)
Segara Anakan in Cilacap regency, Central Java is a wetland area that has mudflat utilized by the group of waterbirds which fluctuates throughout the year. This study evaluated the bird diversity and abundance in the estuarine (Muara Sungai) of Segara Anakan covered by 78 ha of mudflat. The research was conducted on the fine mud to sandy mud habitat type from November 2014 to February 2015. Observations bird census conducted through surveys of water use boats in mud habitats. Its diversity was expressed by Shannon index (H'). There were 23 species of waterbirds recorded during the observation period with a total of 580 individuals. The highest abundance of bird was found in November 2014 which was rainy season (299 individuals; H'1,12) and was dominated by shorebirds (284 individuals) especially Charadrius leschenaultii (226 individuals). However, the least bird abundance was in February 2015 which was the onset dry season (68 individuals; H'2,37) and was dominated by wading birds (38 individuals) mainly Ardea cinerea (15 individuals). Species richness, abundance of bird and Shannon Index diversity (H') is influenced by seasonality and geographic location are supporting their potential fodder for waterbird community at Segara Anakan.Keywords: abundance of individuals, Muara Sungai, Segara Anakan, waterbird